Anthocyanin profile and antioxidant capacity in coloured barley. (16th May 2019) - Suriano, Serafino; Savino, Michele; Codianni, Pasquale; Iannucci, Anna; Caternolo, Giovanni; Russo, Mario; Pecchioni, Nicola; Troccoli, Antonio
Summary: The grain of 17 coloured barley F8 recombinant inbred lines from three backcross programs using three barley parental lines were studied. The main objectives were to characterise the anthocyanin profiles and antioxidant activities of these different lines of coloured barley grain when grown in southern Italy. HPLC and spectrophotometric analyses were performed. The overall profile of anthocyanins across the grain of these genotypes comprised 51.8% malvidin 3‐glucoside, 12.7% delphinidin 3‐glucoside, 5.0% cyanidin, ~2.5% both petunidin and peonidin 3‐glucoside, and ~1.4% both delphinidin 3‐rutinoside anthocyanidin 3‐glucoside, with the remaining 23% as unidentified anthocyanins. Principal component analysis showed that the antioxidant activities of the barley grain were significantly correlated with the levels of phenolic compounds. Furthermore, the grain of some of these coloured barley RILs had the highest radical scavenging activities, which indicated their potential use in preparation of both food and nutraceuticals, for protective effects on human health, and in breeding programs. Abstract : Experimental approach for the characterization of anthocyanin profile of Italian coloured barley.